Manipulation of ABA Content in Arabidopsis thaliana Modifies Sensitivity and Oxidative Stress Response to Dickeya dadantii and Influences Peroxidase Activity - Van Gijsegem, Frédérique; Pédron, Jacques; Patrit, Oriane; Simond-Côte, Elizabeth; Maia-Grondard, Alessandra; Pétriacq, Pierre; Gonzalez, Raphaël; Blottière, Lydie; Kraepiel, Yvan (Frontiers in Plant Science, 2017)
The production of reactive oxygen species (ROS) is one of the first defense reactions induced in arabidopsis in response to infection by the pectinolytic enterobacterium Dickeya dadantii. Previous results also suggest that abscisic acid (ABA) favors D. dadantii multiplication and spread into its hosts. Here, we confirm this hypothesis using ABA-deficient and ABA-overproducer arabidopsis plants. We investigated the relationships between ABA status and ROS production in arabidopsis after D. dadantii infection and showed that ABA status modulates the capacity of the plant to produce ROS in response to infection by decreasing the production of class III peroxidases. This mechanism takes place independently of the well-described oxidative stress related to the RBOHD NADPH oxidase. In addition to this weakening of plant defense, ABA content in the plant correlates positively with the production of some bacterial virulence factors during the first stages of infection. Both processes should enhance disease progression in presence of high ABA content. Given that infection increases transcript abundance for the ABA biosynthesis genes AAO3 and ABA3 and triggers ABA accumulation in leaves, we propose that D. dadantii manipulates ABA homeostasis as part of its virulence strategy.